Degradación de Acetaminofén en matrices acuosas por medio de bacterias endófitas provenientes del cultivo de lechuga (Lactuca sativa) - Paez Almanza, Valentina (Universidad Antonio Nariño, 2023)
The presence and persistence of pharmaceuticals in the food chain, especially in food crops, can have negative effects on human health and the environment. Acetaminophen in particular is a significant environmental pollutant due to its widespread use. The objective of this work was to determine the degradation of acetaminophen (ACE) by endophytic bacteria from lettuce from 3 municipalities of the Sabana de Bogotá (Cota, Mosquera and Funza). For this purpose, lettuce endophytes were selected in minimal salt medium containing acetaminophen, drug degradation was performed by HPLC, and bacteria were identified by 16s rRNA gene sequencing. The bacteria Klebsiella sp L1cp and Klebsiella pneumoniae L2cp use acetaminophen as a carbon and energy source for their growth. Strains L1cp and L2cp degraded 20% and 70% of acetamiphone at 50 mg/l in 60 h. Glucose addition affected ACE degradation, with L1cp degradation increased by 33% and L2cp degradation decreased by 53%. These results suggest the potential of lettuce endophytic bacteria to degrade acetaminophen and a possible mechanism of protection or detoxification of exogenous substances in plants.